2010
DOI: 10.1111/j.1439-0531.2010.01726.x
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Total Proteins and Albumins, and AST, AP, CK and GGT Activities in the Blood Serum Boer and Saanen Goats During Puerperium

Abstract: The metabolism of proteins in the blood serum in Boer and Saanen goats was investigated during puerperium. Twenty Boer goats (10 primiparous and 10 pluriparous) and 10 Saanen goats (five primiparous and five pluriparous) between 2 and 5 years of age were used in this research. Blood for analysis was taken every fourth day from day 3 until day 40 post-partum. Blood samples were collected by jugular puncture. In the obtained blood serum, the concentration of total proteins (PT) and albumin (ALB), and the activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 10 publications
4
12
1
1
Order By: Relevance
“…The AST activity found in this research in both periods was significantly lower than the literature reference values (KANEKO et al, 2008), and according to PICCIONE et al (2010) for Girgentana goats. The AST activity did not alter significantly in the two research periods, as found for Saanen and Boer goats by DJURIČIĆ et al (2011). Unlike ANTUNOVIĆ et al (2011) the total bilirubin levels were higher during early lactation than in early pregnancy, and altogether higher than the reference values found in the literature (KANEKO et al, 2008), as mentioned by LEPHERD et al (2009) for Merino ewes.…”
Section: Discussioncontrasting
confidence: 48%
“…The AST activity found in this research in both periods was significantly lower than the literature reference values (KANEKO et al, 2008), and according to PICCIONE et al (2010) for Girgentana goats. The AST activity did not alter significantly in the two research periods, as found for Saanen and Boer goats by DJURIČIĆ et al (2011). Unlike ANTUNOVIĆ et al (2011) the total bilirubin levels were higher during early lactation than in early pregnancy, and altogether higher than the reference values found in the literature (KANEKO et al, 2008), as mentioned by LEPHERD et al (2009) for Merino ewes.…”
Section: Discussioncontrasting
confidence: 48%
“…The ALAT is considered one of the most sensitive enzymes in the diagnosis of hepatocellular injury (Tibbo et al 2008). In our study, the values for the plasma concentrations of γ-GT and ALAT were close to the value ranges (20−50 IU/l for γ-GT and 15.3−52.3 IU/l for ALAT, respectively) of Tibbo et al (2008) and Djuricic et al (2011).…”
Section: Plasma Lipid Profile and Enzymatic Activitiesmentioning
confidence: 59%
“…The γ-GT is a membrane-bound enzyme, found in tissues with high rates of secretion or absorption, among the most notable being the liver (Djuricic et al 2011). The γ-GT activity increases as a result of damage to the cellular structures of hepatocytes (Lubojacka et al 2005).…”
Section: Plasma Lipid Profile and Enzymatic Activitiesmentioning
confidence: 99%
“…It has been suggested that metabolism of protein plays an important role in the regulation of physiological functions during the perinatal period [2,6]. Additionally, the activity of aminotransferases in blood is very important for the metabolism of amino acids and carbohydrates; thus, the increased aminotransferase activity in the blood (reflected as increased AST in our study) might have been a consequence of increased activity within normal reference values in the cells or cell structural damage, as previously reported [2,6]. Therefore, the results of these comparisons between good and poor groups may indicate essential patterns in our established MPT system for achieving improved reproductive performance in the breeding cattle herds in our region.…”
Section: Discussionmentioning
confidence: 99%